Point cloud slicing for 3-D printing. Issue 1 (2nd January 2018) - Oropallo, William; Piegl, Les A.; Rosen, Paul; Rajab, Khairan
ABSTRACT: This paper revisits a more than half a century old problem: slice a free-form object into layers for manufacturing. A point based approach is taken that would have been prohibitive even a decade ago. Due to modern hardware, plenty of storage and a plethora of software packages, the time has come to ditch complicated and error prone numerical code and deploy a simple point based method to achieve robustness and accuracy that have been lacking for a very long time. GRAPHICAL ABSTRACT: